(untitled) (Dhaka University Journal of Science, 2020)
Investigation of meteorological conditions favorable for formation of pre-monsoon thunderstorm over Bangladesh has been conducted by simulating a selected thunderstorm case using ARW dynamic core of WRF model (WRF-ARW). A multi-cell thunderstorm formed on 30-03-2018 over the northwestern tip of Bangladesh and adjacent territories of India and moved south-southeast wards with its highest development at 09:30 UTC was selected for this study. The chosen case of thunderstorm has 3 distinct cells of which 2 cells have the width of over 100 km each and the third one located in the eastern Bangladesh and had the width of 50 km. A WRF ARW model has been applied to examine the atmospheic characteristics favorabe for genesis of selected case run in a double nested domain of resolution of 9x9 km2 in the outer domain and 3 3 km2in the inner domain. The analysis of the geopotential height field of 925 hPa level generated by WRF model at different hours of 31 March 2018 clearly indicates favourable condition with pockets of micro lows and their progression towards central to southeastern Bangladesh. The strong winds blowing from Bay of Bengal along an anticyclone over the Bay brings sufficient moisture to the north. The southerly winds meet the easterly and also westerly winds providing strong low level convergence which favors the convective activities forming cumulus cells. The orography of foothills may also enhance the convections. The wind in the upper tropospheric winds attains jet speed over these areas. The distribution of divergence and vorticity in the 925 hPa level shows the evolution of system. The distribution of precipitation shows that the spatial patterns were well captured. Vertical velocity has been plotted along the vertical-horizontal plane oriented in the east-west direction across a high rainfall cell. This shows that the highest development of narrow vertical cell extends up to 100 hPa level. Following the temporal evolution of the system, it is seen that the highest development delayed by around 2 hours. Some mitigation strategies in respect of thunderstorms and associated lighting are also discussed. Dhaka Univ. J. Sci. 68(1): 71-77, 2020 (January)